Computational and experimental study of an ion injector of a weakly divergent ion beam for implementing a method for removing space debris objects by an ion beam. (March 2023) - Melnikov, A.V.; Bogachev, E.A.; Elakov, A.B.; Mogulkin, A.I.; Obukhov, V.A.; Perminova, YuS.; Peysakhovich, O.D.; Pokrishkin, A.I.; Svotina, V.V.; Cherkasova, M.V.
Abstract: Attention to the method of removing large space debris objects by impacting them with an ion beam has not waned over the past 10 years. The application of this method to the space debris removal from the protected area of the Geostationary Earth Orbit (GEO) seems to be the most effective. This is due to a low energy consumption for removing an object to a safe orbit with ΔV≃11 m/s, which allows the removal of several objects by a single spacecraft. A service spacecraft can be developed for this purpose based on the TelSat geostationary communication satellite technology. At the same time, one of the problematic issues remains that is the development of an injector of a weakly divergent ion beam. The ion beam divergence during injection into the vacuum occurs under the insuperable influence of the ambipolar electric field acting in the beam volume. At the same time, the beam behavior depends on the initial divergence angle stipulated by the conditions of beam formation by the electrostatic acceleration system. This paper considers the results of calculated and experimental studies for the peculiarities of the formation of an ion beam in an ion extraction system with slit and round apertures. The dependence of the initial divergence half-angle on the beam perveance for both geometries was defined. In the operation of the injector designed for the space debris removal, it is necessary to ensure stability of the geometry of the ion-extraction system, which is subject to uneven thermal loading. The resulting thermomechanical deformations of the grids in the technology of ion thrusters are parried by giving the grids a plate shape. Therefore, flat grids made of a carbon-carbon composite material of a new type were used in experiments, which avoided noticeable deformations. The results of experimental investigation of the prototype of ion injector with two configurations of carbon grids (with round and slit perforation) and with the initial divergence half-angle of 2°-4° are given in this paper. The thrust control of an ion beam by changing of the screen grid potential under the condition of a constant beam perveance is considered. It is shown that such regulation is associated with a change in the Mach number, which affects the beam divergence. As an example, the calculation of the dependence of the coefficient k on the distance to the removing object is given, which is considered to be a spent satellite SUPERBIRD-A. Highlights: The minimum angle of the ion beam divergence of the ion injector were achieved. A comparison of ion injector with slit-type and round-type aperture perforation. The value of coefficient of thrust transfer to the object to be removed.